Rapid rural appraisal of a rural village in Sabah. - Chua, Philip Yi Shean; Lee, Sue Laine; Tow, Zhen Jiang; Richmund Mantok,; Muhamad Khairul Hawari Muhamad Nor,; Lavena Dorairaja,; Jack, Javier; Nur Fadhilah Rusly,; Nursyafina Mohamad Hanafi,; Thant Zin, (Universiti Kebangsaan Malaysia, 2013)
Rapid Rural Appraisal (RRA) is a systematic, semi-structured activity carried out in the field by a multidisciplinary team that is designed to obtain new information and hypotheses about rural life. This article reports the results of an RRA conducted in Kampung Paris 1 (KGP1), Kinabatangan, Sabah under the Annual Health Promotion Program of the School of Medicine, Universiti Malaysia Sabah.